A Tissue‐Penetrating Double Network Restores the Mechanical Properties of Degenerated Articular Cartilage. (2nd March 2016) - Cooper, Benjamin G.; Stewart, Rachel C.; Burstein, Deborah; Snyder, Brian D.; Grinstaff, Mark W.
Abstract: Incorporation of an interpenetrating polymer network into an existing single polymer network enables augmentation of the original substrate's mechanical properties, and translation of this concept from purely synthetic materials to natural–synthetic hybrid systems provides the opportunity to reinforce mechanical properties of bulk biological substrates. In many disease states, the mechanical properties of bodily tissues deteriorate rendering them prone to further material failure. Herein, a tissue‐supplementing technique is described in which an interpenetrating biomimetic hydrogel is polymerized in situ throughout cartilage tissue. The treatment restores the inferior compressive properties of osteoarthritic cartilage to that of healthy cartilage, preferentially localizing to weaker regions of tissue. Furthermore, the treatment technique preserves cartilage under harsh articulation conditions, showing promise as a materials‐based treatment for early‐stage osteoarthritis.